2012
DOI: 10.1021/jo302146r
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Cyclizations of 1-R-Ethynyl-9,10-anthraquinones: Use of Thiourea as a “S2–” Equivalent in an “Anchor-Relay” Addition Mediated by Formal C–H Activation

Abstract: The EtONa-mediated reaction of peri-R-ethynyl-9,10-anthraquinones with thiourea yields 2-R-7H-dibenzo[de,h]quinolin-7-ones and 2-R-anthra[2,1-b]thiophene-6,11-diones. Although 2-R-7H-dibenzo[de,h]quinolin-7-ones were observed previously in reactions with other N-centered nucleophiles (hydrazine, guanidine, and urea), the formation of 2-R-anthra[2,1-b]thiophene-6,11-diones is a new reactivity path. DFT computations analyzed factors responsible for the switch in reactivity and the relative importance of two poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The sodium‐ethoxide‐mediated formation of 2‐R‐anthra[2,1‐b]thiophene‐6,11‐diones was developed through the direct CH activation of peri‐R‐ethynyl‐9,10‐anthraquinones with thiourea (Scheme ) 69…”
Section: Cs Bond Construction By Different Sulfuration Agentsmentioning
confidence: 99%
“…The sodium‐ethoxide‐mediated formation of 2‐R‐anthra[2,1‐b]thiophene‐6,11‐diones was developed through the direct CH activation of peri‐R‐ethynyl‐9,10‐anthraquinones with thiourea (Scheme ) 69…”
Section: Cs Bond Construction By Different Sulfuration Agentsmentioning
confidence: 99%
“…The Sonogashira reaction, which features the cross-coupling of iodine-or bromine-substituted 9,10-anthraquinone and diverse terminal acetylenes, has become the main method for synthesizing acetylene derivatives of quinones in recent years. Through this reaction, a wide range of perisubstituted acetylenyl-9,10-anthraquinones have been prepared via the simple condensation of 1iodo-9,10-anthrachine with various terminal acetylenes, including alkynes with aryl, hetaryl, and aliphatic substituents with both donor and acceptor systems, in the presence of a metal complex such as PdCl 2 (PPh 3 ) 2 -CuI-PPh 3 [6,7] (Figure 1). Generally, the cross-coupling reaction proceeded smoothly, and the yields of the alkynylquinone products were between 80 and 98 %.…”
Section: Synthesis Of Acetylenequinonesmentioning
confidence: 99%
“…It was revealed that the ratio of the products from the reaction with guanine was caused by the occurrence of three competing types of cyclization reactions, namely, the attack of both the nucleophilic 6endo and 5-exo derivatives on the electrophilic alkyne fragment and the 6-exo-cyclization reaction in which the alkine acted as a nucleophile. A study on the reactivity of the dyad peri-ethynylanthraquinone-thiourea was of particular interest since the presence of two different nucleophilic centers (S and N) in the reagent brought into question the overall chemoselectivity of the reaction [7]. It was found that the interaction between 1-R-ethynyl-9,10-anthraquinone analogs of 1 and excess thiourea in boiling pyridine for 8 to 26 h under the influence of sodium ethylate resulted in the formation of two heterocyclic products, namely, analogs of 2-R-7H-dibenzo[de,h]quinolin-7-one 2 and analogs of 2-R-anthra[2,1-b]thiophen-6,11-diones 3 with a predominance for the latter.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…14 Intermolecular cyclizations of 1-alkynyl-9,10-anthraquinones (continued) Similarly, the hydrolysis of ester 13 under basic conditions and subsequent intramolecular Friedel-Crafts reaction of the intermediate acid gave the desired derivative 10c. 16 The reaction of 1-alkynyl-9,10-anthraquinones 1a,b,d-h with thiourea (method I) effected by NaOEt in refluxing pyridine yielded the desired dibenzo[de,h]quinolin-7-ones 2a,b,d-h and anthra[2,1-b]thiophene-6,11-diones 4a,b,d-h. 12 Heating of alkynes 1a-f,i-k with an excess of urea (method II) led to a regiospecific reaction producing the dibenzo[de,h]-isoquinolin-7-ones 2a-f,i-k. 13 The interaction of guanidine with alkynylanthraquinones 1a,d,e,i,l-n in refluxing n-butanol proceeded with the Another route includes the hydrolysis of cyanophenylisoquinoline 12 by 40% KOH in EtOH. Heating of the intermediate 9b with polyphosphoric acid at 100°C led to compound 10b.…”
Section: Intramolecular Cyclizations Of Isoquinolinesmentioning
confidence: 99%